Pengaruh Kompensasi, Motivasi, Dan Gaya Kepemimpinan Terhadap Kepuasan Kerja Karyawan di PT. United Equipment Indonesia - Sinaga, Gilbert Johan Martin (AKUNTANSI 45, 2025)
This study aims to analyze the effect of compensation, motivation, and leadership style on employee job satisfaction at PT United Equipment Indonesia, Pekanbaru. Job satisfaction is an important factor that can affect employee productivity and loyalty in an organization. This research uses a quantitative approach with a survey method through distributing questionnaires to employees of PT United Equipment Indonesia. Data analysis was conducted using multiple linear regression to determine the relationship between the independent variables (compensation, motivation, and leadership style) with the dependent variable (job satisfaction). The results showed that the three independent variables had a significant effect on employee job satisfaction. Among the three variables, motivation has the most dominant influence compared to compensation and leadership. This indicates that the higher the level of motivation given to employees, the higher their level of job satisfaction. In addition, a fairer compensation system and an effective leadership style were also shown to significantly increase employee job satisfaction. These findings lead to several recommendations for companies to increase employee job satisfaction, such as improving the compensation system to make it more competitive, improving motivation strategies through rewards and training, and strengthening leadership that is more participatory and communicative. Thus, companies can increase employee retention and reduce high turnover rates.